Decree of the President of the Arab Republic of Egypt No. 126 of the Year 2010 Concerning Extending The State Of Emergency To Face Terrorism = قرار رئيس جمهورية مصر العربية رقم 126 لسنة 2010 بمد حالة الطوارئ لمواجهة أخطار الإرهاب - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic.